Biological invasions forming intraguild predation communities in homogeneous and heterogeneous landscapes - Poloni, Silas [UNESP]; Kraenkel, Roberto André [UNESP]; Mendes Coutinho, Renato (Springer Nature, 2025)
Intraguild predation (IGP) allows for coexistence between two consumers of a single resource, as long as the intraguild prey (IG prey) is competitively superior to the intraguild predator (IG predator) and resource population productivity is neither abundant or limiting. Here, we explore biological invasions forming IGP community modules by either introducing IG prey or IG predator species to established consumer-resource populations in homogeneous and heterogeneous landscapes, using reaction-diffusion equations as our modeling framework. Our main methods of analysis are comparing numerical solutions to linearization techniques and homogenization approximations. We find that in homogeneous landscapes, speeds are linearly determinate, i.e., depend on low invader population densities at the leading edge. We also find traveling wave solutions and dynamical stabilization regimes. On heterogeneous landscapes, our results show that depending on habitat preferences of the three species involved, coexistence regimes can occur regardless of IG-prey being least effective consumer, or be hindered even when IG-prey remains as the dominant competitor. Our work assesses how fast can organisms invade novel landscapes in presence of a established IG prey or IG predator and also demonstrates how habitat fragmentation and species habitat preference can disrupt or facilitate coexistence in IGP communities.
Keywords: Mathematical models; Population dynamics; Reaction-diffusion equations; Spatial ecology